The ecological footprint as a sustainability metric : implications for sustainability - Thornbush, Mary J. 1974- (Springer, 2021)
This book examines the Ecological Footprint and biocapacity accounting within an applied development content for Costa Rica. By doing so, it is possible to track changes as well as perhaps link these to overarching global issues, such as trade, globalization, and food security, among other emergent topics based findings stemming from this methodology. Based on a timeseries since 1961, it is possible to track cross-temporal changes of land-type categories (for crop land, grazing land, forest land, fishing ground, built-up land, and carbon) of the Ecological Footprint and biocapacity conveying whether a country is in ecological deficit and what may be contributing to such a trend.
Keywords: Environmental economics -- Costa Rica -- Case studies.; Nature -- Effect of human beings on -- Costa Rica -- Case studies.; Environmental responsibility -- Costa Rica -- Case studies.; Sustainable development -- Costa Rica -- Case studies.; Economic development -- Environmental aspects -- Costa Rica -- Case studies.; Human ecology -- Costa Rica -- Case studies.; Sustainable development.; Natural resources.; Environmental management.; elektronické knihy; electronic books